A Hierarchical Pitman-Yor Process HMM for Unsupervised Part of Speech Induction. - Blunsom, P; Cohn, T (Association for Computer Linguistics, 2011)
In this work we address the problem of unsupervised part-of-speech induction by bringing together several strands of research into a single model. We develop a novel hidden Markov model incorporating sophisticated smoothing using a hierarchical Pitman-Yor processes prior, providing an elegant and principled means of incorporating lexical characteristics. Central to our approach is a new type-based sampling algorithm for hierarchical Pitman-Yor models in which we track fractional table counts. In an empirical evaluation we show that our model consistently out-performs the current state-of-the-art across 10 languages. © 2011 Association for Computational Linguistics.